Confinement-induced Ni-based MOF formed on Ti3C2Tx MXene support for enhanced capacitive deionization of chromium(VI) - Xiaofei Zhang; Zheng Wang; Xuejie Guo (Scientific Reports)
Abstract MXenes, as a novel two-dimensional lamellar material, has attracted much attention. However, MXenes lamellar are prone to collapse and stacking under hydrogen bonding and interlayer van der Waals forces, which affects their electrochemical and capacitive deionization performance. A three-dimensional Ni-1,3,5-benzenetricarboxylate/Ti3C2Tx (Ni-BTC/Ti3C2Tx) composite electrode material was developed to enhance the electrochemical and capacitive deionization performance. The uniformly decorated Ni-BTC can prevent MXenes from aggregation and provide a large specific surface area and rich pore structure. As a substrate supporting Ni-BTC, MXenes can effectively disperse the growth of Ni-BTC and enhance the ion transport rate. In addition, the unique three-dimensional structure of Ni-BTC/Ti3C2Tx provides horizontal charge transfer paths like two-dimensional nanosheets and has unique vertical charge transfer paths between nanosheets. Therefore, the Ni-BTC/Ti3C2Tx exhibits an exceptional chromium(VI) removal rate of 94.1%. The electrosorption capacity of the Ni-BTC/Ti3C2Tx for chromium(VI) is 124.5 mg g−1, much higher than that of the pure Ti3C2Tx (55.5 mg g−1). The superior CDI efficiency accomplished through the Ni-BTC/Ti3C2Tx electrode is due to the unique three-dimensional network structure and synergistic effect of the pseudocapacitance generated by the unique assembly of Ni-BTC and Ti3C2Tx. Ni-BTC/Ti3C2Tx is a promising CDI electrode material that can be used for capacitive deionization.